Assessing factors hindering feasibility and build programmes of nuclear power in South Africa - Masutha, Thendo Yeolaine (University of the Witwatersrand, Johannesburg, 2025)
The nuclear energy industry in South Africa has faced various challenges that have hindered its development. This study examines the factors contributing to the slow expansion of the nuclear energy capacity within South Africa’s energy mix, focusing on key barriers such as policy inconsistencies, financial constraints, and technical limitations. It also aims to form recommendations for an improved South African nuclear energy sector. The study is framed within the conceptual context of energy policy, sustainable development, and the just energy transition. The study employs the qualitative approach of case studies and semi-structured interviews as forms of data collection. It explores successful case studies from France and India, where consistent energy policies, strong state support, and strategic funding have enabled substantial growth in their respective nuclear energy sectors. This comparative analysis provides practical recommendations for South Africa, focusing on the importance of improving regulatory frameworks, enhancing financial support mechanisms, and fostering innovation, technical capacity, and improved stakeholder management. Additionally, data were collected from a purposively selected sample of experts in the South African nuclear energy industry. Thereby utilising semi-structured interviews to gain a comprehensive understanding of the challenges faced. The findings highlight several critical barriers, including inadequate policy frameworks, limited financial incentives, a lack of technical expertise, and poor stakeholder engagement. South Africa has the potential to significantly expand its nuclear energy capacity, but this requires targeted interventions to address the existing barriers. The conclusion emphasizes the need for a coordinated approach between government, industry, and stakeholders to create a conducive environment for the development of the country’s nuclear energy sector.
A research report submitted in fulfillment of the requirements for the Master of Management in Energy Leadership, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Nuclear energy; South Africa; sustainability; Koeberg Power Station; SDG-7: Affordable and clean energy; SDG-9: Industry, innovation and infrastructure